MAKNA SIMBOLIK TUJUH UMBUT DALAM TRADISI NUJUH HARI PASCA KEMATIAN PADA MASYARAKAT DESA KARANG TANDING KECAMATAN PENUKAL UTARA KABUPATEN PALI - Sartika Ade Sari; Nur Fitriyana (Jurnal Studi Agama, 2021)
Death is something that everyone experiences. Man does not know when he died. Every society has a different tradition in commemorating the day of the dead. The people of Karang Tanding Village always serve seven umbut on the seven days of death. So this research is important to find out the symbolic meaning and people's views about the seven umbut cuisine in the tradition of nujuh days after death. The type of research used is field research). Types of qualitative data The data sources in this study consist of primary data and secondary data. Primary data were obtained directly from religious leaders, traditional leaders and the community of Karang Tanding Village by interview and documentation. Secondary data is taken from books and journals related to the problem being studied. Data collection techniques in this thesis are observation, interviews, and documentation. The data analysis techniques in this thesis are data reduction, data presentation, and verification. This study resulted in the finding that the symbolic meaning of the seven umbuts is to pray for the dead in the hope that good deeds and deeds performed during life can continue to provide benefits not only to the deceased, but also to children, families and communities. This tradition is a form of respect for the ancestral spirits of the ancestors of the Karang Tanding village. The people of Karang Tanding village view the tradition of seven umbut cuisine in the implementation of the tradition of seven days after death as a legacy of tradition and does not violate religious teachings. This tradition is seen as a prayer, homage to ancestral spirits and as consolation for bereaved families. The tradition is still carried out because it does not burden residents and seven umbut are used as the main menu.